Implementation of the Pancasila Lima Dasar Game in English Learning to Improve Vocabulary of Students in SB Hulu Langat, Malaysia - Putri Ainun Niza; Gunawan; Dewi Sartika (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This article examines the implementation of the "Pancasila Lima Dasar" game in English language learning at the Hulu Langat Guidance Studio, Malaysia as one of the interactive learning methods to improve English vocabulary for students in grades 4, 5, and 6. With a descriptive qualitative approach that describes the implementation process and the development of activities and their impact on student vocabulary. Some students showed an increase in vocabulary although there were still differences in their ability to grasp the learning. With this Activity, immigrant students abroad are expected to be able to provide a new understanding of the development of interactive learning methods. Games are a learning method that is widely used by teachers when teaching. In language subjects, many types of games can be used to improve students' vocabulary. This game is played in groups by sitting in a circle and taking turns mentioning vocabulary according to the specified letters.